(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A simple, accurate, precise method was developed to simultaneously estimate the bempedoic acid (BEM) and ezetimibe (EZT) in bulk and pharmaceutical dosage form using RP-UPLC. Combination of bempedoic acid and ezetimibe is used to treat adults with heterozygous familial hypercholesterolemia or established atherosclerotic cardiovascular disease. Chromatographic separation was carried out using X-Bridge phenyl 150 x 4.6 mm, 3.5 μ column at a 1.0 mL/min flow rate. The mobile phase consisted of 0.1% formic acid buffer and acetonitrile (70:30%v/v). The retention times of BEM and EZT were found to be 1.157 and 3.208 minutes, respectively. The temperature was maintained at ambient. The optimized wavelength for BEM and EZT was 230 nm. The method developed has been statistically validated according to ICH guidelines. %RSD of BEM and EZT were and found to be 0.6 and 1.4, respectively. %Recovery was obtained as 100.0% and 101.40% for BEM and EZT, respectively. LoD, LoQ values were obtained from regression equations of Bempedoic acid and Eetimibe were 0.27 μg/mL, 0.015 μg/mL and 2.7 μg/mL, 0.15 μg/mL respectively. The method obeys Beer’s law in the concentration range of 27–337.5 μg/mL (R2 = 0.9991) for BEM, and 1.5–18.75 μg/mL (R2 = 0.9993) for EZT. The method showed good reproducibility and recovery with %RSD less than 2. Forced degradation studies established the stability-indicating capability of the method under stress conditions like acid, base, peroxide, UV, thermal, humidity. Retention times were decreased and that run time was decreased. Hence, the chromatographic method developed was simple and economical and can be adopted in regular quality control test in Industries. It is said to be rapid, specific, sensitive, robust, and reliable and can be effectively applied for routine analysis in research institutions, quality control departments in industries.